The Epistemology of Moderate Fiqh: A Study of Yusuf Al-Qaradhawi’s Thought on Islamic Legal Reasoning - Kambang Muhammad Syahdan; Intan Nuraini; Zahrotul Firdaus; M. Barokatul Makky; Ahmad Riziq Akbar; Khansa Rufaida Zia; Aulia Rizqi Febriananda (TATHO: International Journal of Islamic Thought and Sciences, 2026)
This qualitative research, conducted as a literature review, aims to identify Yusuf Qardhawi’s views on the urgency of ijtihad in formulating moderate Islamic law. The primary data used is the book by Saifullah M. Yunus titled *Opening the Doors of Ijtihad*. Secondary data draws upon various relevant scholarly works. The results of the study indicate that Yusuf Qardhawi emphasizes the importance of a moderate fiqh paradigm in addressing contemporary Islamic legal issues a paradigm grounded in sharia evidence, logic, and the public interest. Some modern issues discussed in his fatwas include abortion, marriage, and Islamic banking. This study contributes to the assertion that Yusuf Qardhawi’s thought plays a significant role in the development of Islamic fiqh through a moderate approach that balances religious texts with current realities.